Tuning BRCA1 and BARD1 activity to investigate RING ubiquitin ligase mechanisms. (23rd January 2017) - Stewart, Mikaela D.; Duncan, Emily D.; Coronado, Ernesto; DaRosa, Paul A.; Pruneda, Jonathan N.; Brzovic, Peter S.; Klevit, Rachel E.
Abstract: The tumor‐suppressor protein BRCA1 works with BARD1 to catalyze the transfer of ubiquitin onto protein substrates. The N‐terminal regions of BRCA1 and BARD1 that contain their RING domains are responsible for dimerization and ubiquitin ligase activity. This activity is a common feature among hundreds of human RING domain‐containing proteins. RING domains bind and activate E2 ubiquitin‐conjugating enzymes to promote ubiquitin transfer to substrates. We show that the identity of residues at specific positions in the RING domain can tune activity levels up or down. We report substitutions that create a structurally intact BRCA1/BARD1 heterodimer that is inactive in vitro with all E2 enzymes. Other substitutions in BRCA1 or BARD1 RING domains result in hyperactivity, revealing that both proteins have evolved attenuated activity. Loss of attenuation results in decreased product specificity, providing a rationale for why nature has tuned BRCA1 activity. The ability to tune BRCA1 provides powerful tools for understanding its biological functions and provides a basis to assess mechanisms for rescuing the activity of cancer‐associated variations. Beyond the applicability to BRCA1, we show the identity of residues at tuning positions that can be used to predict and modulate the activity of an unrelated RING E3 ligase. These findings provide valuable insights into understanding the mechanism and function of RING E3 ligases like BRCA1.